LIFE AND WORK DEDICATED TO AESTHETICS AND CULTURE Academician Georgi STARDELOV (August 28, 1930 - January 11, 2021) (Annual of the Faculty of Philosophy in Skopje, 2021)
Death is a relentless fact that silently contradicts us and warns us to be silent because words are never enough to express our sorrow for the one who is no longer with us with his body, but death, at the same time, causes us to speak, because at the beginning of everything is the word and because the word is at the end - he is the alpha and omega of our entire culture and civilization. And exactly to the word and the thought, to the logos from which everything starts and to which everything ends in the end, in fact, the life and work of academician Georgi Stardelov were entirely dedicated, because he, as a philosopher and aesthetician, as a philosopher of culture and literary a critic, as a top hermeneutist, found the meaning of his tireless scientific and social activity precisely in his words, in their meanings, and in their activity.